The Symbolic and Cultural Meaning Behind The Virality of “Dame Un Grr” On Social Media: Makna Simbolik dan Budaya dibalik Viralitas “Dame Un Grr” di Media Sosial - Alfi, Alfiana Yuniar Rahmawati (Kanal: Jurnal Ilmu Komunikasi, 2025)
The increasing public engagement in the 2024 Garut regional election campaign for the Syakur-Putri pair reflects a shift in how the public responds to local political communication. This campaign was conducted through two main channels: direct interactions such as community visits and field outreach, and massive digital campaigning via social media targeting young voters and marginalized groups. This study aims to analyze the effectiveness of the Syakur-Putri political campaign in fostering public engagement through the four dimensions of the Situational of Publics theory: problem recognition, constraint recognition, level of involvement, and referent criterion. A descriptive qualitative method was employed using observation, literature review, documentation, and in-depth interviews with the core campaign team, local media observers, and political party representatives. The results show that the campaign successfully mobilized the public from passive awareness to active participation. High levels of engagement were influenced by information transparency, responsive digital interaction, and the candidates’ simple and authentic image. The problem recognition dimension indicated that the public identified real issues such as infrastructure, education, and gender empowerment. In constraint recognition, external barriers were addressed through inclusive communication. The level of involvement reflected strong offline and online participation. Lastly, the referent criterion revealed strong social identification with the local values represented by the candidates. A communication strategy grounded in local narratives and relational approaches proved to be the key to campaign effectiveness at the regional level.